Astrocyte-Derived Pentraxin 3 Supports Blood–Brain Barrier Integrity Under Acute Phase of Stroke. Issue 4 (April 2016) - Shindo, Akihiro; Maki, Takakuni; Mandeville, Emiri T.; Liang, Anna C.; Egawa, Naohiro; Itoh, Kanako; Itoh, Naoki; Borlongan, Mia; Holder, Julie C.; Chuang, Tsu Tshen; McNeish, John D.; Tomimoto, Hidekazu; et al.
Abstract : Background and Purpose—: Pentraxin 3 (PTX3) is released on inflammatory responses in many organs. However, roles of PTX3 in brain are still mostly unknown. Here we asked whether and how PTX3 contributes to blood–brain barrier dysfunction during the acute phase of ischemic stroke. Methods—: In vivo, spontaneously hypertensive rats were subjected to focal cerebral ischemia by transient middle cerebral artery occlusion. At day 3, brains were analyzed to evaluate the cellular origin of PTX3 expression. Correlations with blood–brain barrier breakdown were assessed by IgG staining. In vitro, rat primary astrocytes and rat brain endothelial RBE.4 cells were cultured to study the role of astrocyte-derived PTX3 on vascular endothelial growth factor–mediated endothelial permeability. Results—: During the acute phase of stroke, reactive astrocytes in the peri-infarct area expressed PTX3. There was negative correlation between gradients of IgG leakage and PTX3-positive astrocytes. Cell culture experiments showed that astrocyte-conditioned media increased levels of tight junction proteins and reduced endothelial permeability under normal conditions. Removing PTX3 from astrocyte-conditioned media by immunoprecipitation increased endothelial permeability. PTX3 strongly bound vascular endothelial growth factor in vitro and was able to decrease vascular endothelial growth factor–induced endothelial permeability. Conclusions—: Astrocytes in peri-infarct areas upregulate PTX3, which may support blood–brain barrier integrity by regulating vascular endothelial growth factor–related mechanisms. This response in astrocytes may comprise a compensatory mechanism for maintaining blood–brain barrier function after ischemic stroke. Abstract : Supplemental Digital Content is available in the text.